Accelerating Poverty Reduction in Mozambique : Challenges and Opportunities - World Bank Group (World Bank, Washington, DC, 2016)
Over the past two decades Mozambique enjoyed robust and accelerating economic growth, yet strong economic progress only translated into modest poverty reduction. Not only poverty fell at slower pace than expected but the gains in income and consumption growth are unevenly distributed across the country and across groups of people. Some parts of the country –especially the center and the north– account for a disproportionate share of the poor. Overall, urban provinces tend to have lower poverty rates than rural provinces, particularly those in the central and northern parts of the country. Three factors contribute to the low equity outcomes in Mozambique: (i) unequal access to economic opportunities across regions and income groups; (ii) low productivity and market-based growth in agriculture; and (iii) high vulnerability to weather shocks. Growth could have had a much larger impact on poverty reduction in Mozambique if its effects had not been offset by the observed increase in inequality. Accelerating poverty reduction requires addressing structural factors that undermine the inclusiveness of growth. The returns to growth have to be distributed more widely to invest in the most isolated parts of the country in for these regions to be able to seize the economic opportunities brought about by economic expansion and close the gap with the rest of the country. There is a need to deepen the investments in the human, physical and institutional capital of the country. Finally, given the high exposure of Mozambique to natural disasters, it is necessary to strengthen formal and informal risk management systems to avoid that the living standards of the population are highly influenced by major shocks out of their control.